2018
DOI: 10.1042/bsr20180861
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects ofFragaria ananassamethanolic extract in a rat model of cadmium chloride-induced neurotoxicity

Abstract: Cadmium (Cd) is a common environmental toxicant that has harmful effects on plants, animals, and humans. The present study evaluated the protective effects of Fragaria ananassa methanolic extract (SME) on cadmium chloride (CdCl2)-induced neuronal toxicity in rats. Male albino rats were intraperitoneally (i.p) injected with CdCl2 (6.5 mg/kg) for 5 days with or without the SME (250 mg/kg). We measured the levels of Cd, lipid peroxidation (LPO), nitric oxide, glutathione (GSH), and oxidative enzymes such as super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 54 publications
5
31
0
1
Order By: Relevance
“…The potential mechanistic links for the beneficial effect of strawberries may be due in part to the neuroprotective properties of the bioactive in strawberries. In animal models, strawberry consumption improved cognitive function, increased neurogenesis, and insulin-like growth factor-1 signaling, reversed neuronal aging by reducing oxidative stress and ameliorated metal-induced neurotoxicity [12,14,34]. Bioactives in strawberries, including pelargonidin, anthocyanidins, and total flavonoids, are known to have anti-inflammatory and antioxidant properties [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanistic links for the beneficial effect of strawberries may be due in part to the neuroprotective properties of the bioactive in strawberries. In animal models, strawberry consumption improved cognitive function, increased neurogenesis, and insulin-like growth factor-1 signaling, reversed neuronal aging by reducing oxidative stress and ameliorated metal-induced neurotoxicity [12,14,34]. Bioactives in strawberries, including pelargonidin, anthocyanidins, and total flavonoids, are known to have anti-inflammatory and antioxidant properties [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to exacerbate the role of Cd-induced oxidative stress, a mention of the antioxidant molecules used to retrieve its detrimental effects is needed. Indeed, many molecules with well-known antioxidant properties were studied to counteract Cd-induced neural oxidative stress, such as royal jelly [175], flavonoids and polyphenols content in Fragaria ananassa methanolic extract [176], selenium [172,177], zinc [172] and CBD [173] as new emerging antioxidant tools in neurodegenerative disorders [178]. Furthermore, in order to counteract the Cd deleterious effects, some studies highlighted the role of divalent metal ions such as magnesium, calcium, zinc in competing with Cd for the same binding sites [179][180][181].…”
Section: Cadmium and Neuronsmentioning
confidence: 99%
“…It was demonstrated that the use of extracts or juices of pomegranate, strawberries, watermelon, and Garcinia Indica fruit, which are popular in Hindu medicine, led to an improvement in cerebral antioxidative potential. The antioxidative properties of fruit result from the presence of large amounts of phenolic compounds, primarily phenolic acids and catechins, epicatechins, flavan-3-ols, kaempferol, quercetin, and luteolin [132,152]. Apart from the same, the mentioned fruit also contain a number of other substances with known antioxidative properties: vitamins C and E, β-carotene, selenium, and anthocyanins [132,153].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The antioxidative properties of fruit result from the presence of large amounts of phenolic compounds, primarily phenolic acids and catechins, epicatechins, flavan-3-ols, kaempferol, quercetin, and luteolin [132,152]. Apart from the same, the mentioned fruit also contain a number of other substances with known antioxidative properties: vitamins C and E, β-carotene, selenium, and anthocyanins [132,153]. Moreover, red-flesh watermelons also contain lycopene, as well as saponins and tannins [143].…”
Section: Phenolic Compoundsmentioning
confidence: 99%